A Development of the Go Village Application for Guminirejo Village Using a Web-Based Waterfall Method - Rizki, Kharis; Kemal Farouq M; Munif (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Digital transformation has become a strategic step in improving the efficiency and transparency of village bureaucracy. This study focuses on developing the Go Village application to enhance the effectiveness of administrative services in Guminingrejo Village. The research employed the Waterfall model, with data collection techniques carried out through observation and interviews with village officials as well as local residents. The Go Village application offers several key features that support the digitalization of village administrative services. In addition to providing online document submissions such as ID cards, police clearance certificates (SKCK), domicile certificates, family cards (KK), and public complaint services, the application also includes a letter tracking system to monitor the status of requests in real time. For administrators, an automated letter generation feature is provided using TinyMCE, while the village head can apply a digital signature based on barcode scanning to accelerate the document legalization process. Moreover, the application implements Progressive Web App (PWA) technology to improve accessibility across devices and integrates a complaint service feature that enables citizens to provide feedback on service quality. The findings show that the Go Village application successfully accelerates administrative processes, increases service accessibility, and reduces queues at the village office. The letter tracking system further enhances transparency for citizens. However, limitations in the community’s digital literacy remain a challenge that needs to be addressed in future development.